Evaluating the impact of immune checkpoint inhibitors on liver steatosis and function: a retrospective cohort analysis - Schellhammer, Sophie K.; Day, Jessica Quintos; Fan, Run; Ye, Fei; Planz, Virginia; Johnson, Douglas B. (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) are an essential class of immunotherapy drugs for cancer, but their impact on chronic inflammatory conditions remains unclear. Liver attenuation, a non-invasive measure of liver steatosis on CT, offers a way to assess liver inflammation. This study evaluates the impact of ICI therapy on liver attenuation and liver enzyme levels in cancer patients, building on prior research with a larger cohort.MethodsWe conducted a retrospective cohort study of 164 cancer patients treated with ICIs at Vanderbilt University Medical Center between 2017 and 2022. Liver attenuation and enzyme levels (total bilirubin, AST, ALT, and alkaline phosphatase) were analyzed before and after ≥1 year of ICI therapy. Clinical factors such as weight change, liver metastasis, and steroid use were also assessed. Hepatic adverse events were characterized using CTCAE v5.0 criteria.ResultsNo significant changes in liver attenuation were observed from baseline to post-treatment (59.86 ± 8.07 HU vs 59.38 ± 8.36 HU, p = 0.42). Liver enzyme levels also remained stable. Post-treatment liver abnormalities occurred in 23 patients (14.0%), with most being Grade 1 elevations (11.0%). Increased body weight was significantly associated with lower liver attenuation (p < 0.0001), and liver metastasis correlated with higher total bilirubin (p < 0.001) and AST levels (p < 0.01).ConclusionICIs did not significantly change liver attenuation or enzyme levels, suggesting they may not exacerbate liver fat deposition or subclinical injury. Further research with additional imaging modalities is warranted.